Brownlie's principles of public international law - Crawford, James 1948- (Oxford University Press, 2012)
Brownlie's Principles of Public International Law has been the definitive guide to international law for over 40 years. This eighth edition, updated by James Crawford, builds on the reputation of its predecesors, providing outstanding, lucid and up-to-date treatment of all of the main issues in international law today.